Development of an Arduino-Based Paddy Transplanting Mechanism - Mohd Yusof, Ernie Mazuin; Saifullizan, Muhammad Faris; Yahya, Norziana; Amali, Naufal Aniq Khairol; Haris, Nur Fazira; Sani, Mohd Aliff Afira (Journal of Advanced Research Design, 2025)
Transplanting of paddy in rice farming presently is done manually, which is costly, time-consuming, and inefficient, especially for small-scale farmers in Malaysia. To overcome these challenges, this research proposes a prototype of paddy transplanting mechanism with the help of Arduino technology to mechanize and improve the transplanting process. The operations of seedling spacing and timing are controlled by ultrasonic sensors, motor microcontrollers, and a pulse width modulation direct current (PWM DC) motor speed controller in the prototype. The findings revealed that the mechanism was successfully developed. The mechanism also ensured a planting depth of 1 cm and a spacing between seedlings of 16 cm, as opposed to the conventional method, where the depth ranged from 0 cm to 3 cm and the distance between seedlings was 13 cm to 15 cm. Therefore, the system is a viable solution for improving the efficiency of rice farming in Malaysia. In this way, this technology can enhance food security, as well as economic development by improving accuracy and decreasing labour dependency. Future research should be directed to enhance the accuracy of the sensors, reduce energy consumption, and expand the mechanism for extensive use in agricultural fields.